The oral health condition of autists from H.O.P.E. Learning Center, SY 1999-2000 - Paraiso, Arvin E.; Poblete, Melissa A. (Adviser).
The oral health condition of autists is one area of concern in Dentistry that has rarely been tackled. The aim of the study is describe the oral health condition of autists from a particular school, that is, H.O.P.E. Learning Center. An oral examination was done to assess their DMFT/dmft and OHI-S scores. Questionnaires were also given to the parents to determine certain factors that may influence their children's oral health condition.This includes: oral hygiene practices, diet, education and parental supervision. 16 autists were distributed into 3 groups that refer to their stage of dentition. The results yielded mean DMFT/dmft scores of 7, 11 and 12, respectively. While the mean OHI-S scores are 0.38, 1 and 1.5, respectively. It was therefore concluded that the oral health condition of autists in H.O.P.E. is poor in comparison to the national and world standards although their oral hygiene is relatively good.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health--Autistic Children